2024
DOI: 10.1039/d3cp05230c
|View full text |Cite
|
Sign up to set email alerts
|

An α-benzithiazolyl 3-pyrrolyl BODIPY probe for ratiometric selective sensing of cyanide ions and bioimaging studies

Kanhu Charan Behera,
Roshnara Mohanty,
Mangalampalli Ravikanth

Abstract: A simple chromo-fluorogenic chemodosimeter probe, α-benzithiazolyl 3-pyrrolyl BODIPY was synthesized by reacting α-formyl 3-pyrrolyl BODIPY with 2-aminothiophenol in DMF at reflux under basic conditions. The probe was structurally characterized by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…Notably, these observed lifetimes matched those reported for 3-pyrrolyl BODIPYs. 3–8 Similarly, the fluorescence decay of triads 6 and 7 (Fig. S71 and S72†), monitored at 695 nm and 685 nm, respectively, was monoexponentially fitted with lifetimes ( τ ) of 3.11 ns for triad 6 and 2.56 ns for triad 7 , closely matching the singlet-state lifetime reported for 3-pyrrolyl BODIPYs.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Notably, these observed lifetimes matched those reported for 3-pyrrolyl BODIPYs. 3–8 Similarly, the fluorescence decay of triads 6 and 7 (Fig. S71 and S72†), monitored at 695 nm and 685 nm, respectively, was monoexponentially fitted with lifetimes ( τ ) of 3.11 ns for triad 6 and 2.56 ns for triad 7 , closely matching the singlet-state lifetime reported for 3-pyrrolyl BODIPYs.…”
Section: Resultssupporting
confidence: 76%
“…and these functionalized 3-pyrrolyl BODIPYs can be further derivatized to prepare several interesting fluorescent compounds for various applications. 6–10 Others 11–14 and we 3–10 have developed a simple route for synthesizing 3-pyrrolyl BODIPYs. We also showed that the BF 2 unit of 3-pyrrolyl BODIPYs could also be demasked by treating 3-pyrrolyl BODIPYs with Lewis acids such as AlCl 3 and ZrCl 4 to afford tripyrrolyl ligands that can be used to prepare interesting coordination complexes such as 3 .…”
Section: Introductionmentioning
confidence: 99%